Partial discharge classifications: Review of recent progress - Raymond, W.J.K.; Illias, Hazlee Azil; Bakar, Ab Halim Abu; Mokhlis, Hazlie (2015)
It is well known that a correlation exist between the pattern of partial discharge (PD) behavior and the insulation quality. Since different sources of partial discharge have their own unique effects on the degradation of insulation material, it is vital to investigate the relationship between the defect type and the PD to determine the insulation quality. Numerous work had been done to classify partial discharge patterns with variable success. Past research work in partial discharge classification varies greatly in terms of classification techniques used, choice of feature extraction, denoising method, training process, artificial defects created for training purposes and performance assessment. Therefore it is necessary for a literature survey to access the state of the art development in partial discharge classification. (C) 2015 Elsevier Ltd. All rights reserved.